PENGARUH PENDIDIKAN DALAM PENGEMBANGAN KARAKTER SISWA - Nabila Viana Putri; Desty Endrawati Subroto; Bela Isma Fauziah; Melani Melani; Joko Nasrullah (Jurnal Padamu Negeri, 2025)
Character Education which includes self-development is a conscious effort to improve the quality of an individual towards the potentials they have through new experiences and knowledge gained by the individual during their life. The purpose of this study was to determine the effect of character education on self-development in students at SMPN 1 Sumbawa Besar. This study uses a quantitative descriptive approach. The toughest challenge in the world of education in Indonesia is improving the quality of learning to produce graduates who are competitive and able to adapt to change and are creative in solving problems faced. The character education process needs to be fostered early on and must be maximized since elementary school. The purpose of character education in schools is to develop the potential of the heart and conscience of students so that they have a soul and social sensitivity towards themselves, their families and their environment. The function of character education is to develop the basic abilities of students so that they think intelligently, behave with noble character, morals, and do something good, which is beneficial for themselves, their families and society. So that the role of education in the formation of students' character has a very urgent and important position in order to improve students' abilities both in terms of cognitive, affective, and psychomotor abilities, and is able to provide the latest nuances and innovations in each educational unit in interactions between students, with teachers, families and with the surrounding environment.